The Effect of Fraud Opportunity on Occupational Fraud among Insurance Companies in Kenya - Ageke, Eddy; Ratemo, Bonface; Musumba, George (International Journal of Modern Risk Management, 2025)
Purpose: Fraudulent activities in insurance has become common. To address this persistent vulnerability and fill the knowledge gap surrounding the structural and behavioral drivers of such fraud, this study critically examines the effect of fraud opportunity on occupational fraud in insurance companies in Kenya. Methodology: The study adopted the explanatory research design. The target population comprised of the 58 insurance companies that are registered under the Insurance Regulatory Authority (IRA). The validity and reliability of the research instruments was tested before the actual data is collected. The validity and reliability of the research instruments was tested before the actual data is collected. The study adopted stratified random sampling procedure. The sample size for the study was 384 employees. The study collected primary data through Semi –structured questionnaires and interview guides. The data collected was then edited, coded and analyzed using the SPSS v27 statistical software. Descriptive statistical analysis was used to determine mean, standard deviation, frequency counts and percentages which was also be presented in output tables as results. Inferential statistics involved simple and linear regression and correlation analyses. The research findings were presented in tables and graphs. Findings: The findings were both the correlation and regression results (r=0.739, R2=0.547; β=0.884, p<0.05) showed there is a statistically significant relation between fraud opportunity and occupational fraud. Unique Contribution to Theory Practice and Policy: The study recommended that insurance companies should review and reinforce internal control systems to close loopholes that create opportunities for fraud.